Comparing the role of parents in forming male and female adolescents' sexual attitude in Malaysia - Tan, Soon Aun; Yaacob, Siti Nor; Nainee, Sarvarubini (Universiti Malaysia Sabah, 2018)
Optimistic sexual attitude is an important protective indicator serving as a guidance to prevent adolescents from early sexual debut. Parents play an essential role in delivering and transmitting such attitude to their adolescents. Thus far, studies have found the link between parent-adolescent communication in sexual topics and adolescents’ sexual attitude (Turnbull et al., 2008; Diiorio et al., 1999). However, the amount and topics covered in sexual communication may differ between males and females as well as in emphasis from both fathers and mothers (Lou & Chen, 2009; Turnbull et al., 2008). Therefore, this study was intended to identify the unique relationship between parent-adolescent sexual communication and sexual attitude by considering the effect of sex. A total of 241 school-going adolescents from three secondary schools (Mage= 15.07; 52.1% females; 48.4% Malays, 27.1% Chinese, 24.5% Indian) were recruited from Penang, Malaysia through convenience sampling method. Respondents completed a self-administered questionnaire containing Parent-teen Sexual Risk Communication Scale (Hutchinson, 2007) and Sexual Attitude Scale (Yaacob et al., 2009). Results revealed that sexual attitude was found significant with mother-adolescent communication but not with father-adolescent communication. In addition, a significant interaction effect of sex in both father- and mother-adolescent communication and sexual attitude was discovered with its effect significant only for females but not for males. Moreover, communication on sexual related topic practised between parents and daughters made it relevant in forming daughters’ optimistic sexual attitude. Overall, this study provides a foundation for understanding the formation of adolescents’ sexual attitude from the interaction effect of sex and its relation to parent-adolescent sexual communication. Findings of the study support the importance of sex in sexual value transformation between parents and adolescents in order to allow adolescents acquire appropriate sexual attitude towards their sexual well-being advancement.